An appetite for cases - Vega, Gina (2018)
Case usage in business schools was originally introduced by Harvard University. Teaching style has changed, from a teacher-centered approach to a student-centered one, as indicated by “flipped classroom” methodology. This essay presents the characteristics of professor’s performance in classroom. Cases study analysis is mainly established in the English language, a fact which can generate difficulties in its learning, especially if in the Latin-American countries there is a poor level of English as a second language. The International Journal of Instructional Cases is a publication that presents case studies with enough information for due analysis and the learning adequacy.